2011
DOI: 10.1111/j.1474-9726.2011.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐15 preferentially enhances functional properties and antigen‐specific responses of CD4+CD28null compared to CD4+CD28+ T cells

Abstract: SummaryOne of the most prominent changes during T-cell aging in humans is the accumulation of CD28 null T cells, mainly CD8+ and also CD4+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 55 publications
2
41
1
Order By: Relevance
“…Despite the high levels of anti-CMV antibodies and the high frequencies of CD28 null T cells, we found no association between CMV infection and TNF-␣ levels in the sera of elderly individuals. There was a significant correlation with the level of IL-15, another cytokine implicated in the loss of CD28 expression in CD8 ϩ T cells and an inducer of preferential proliferation and functional capabilities of CD4 ϩ CD28 null T cells (20,37).…”
Section: Cd28mentioning
confidence: 90%
“…Despite the high levels of anti-CMV antibodies and the high frequencies of CD28 null T cells, we found no association between CMV infection and TNF-␣ levels in the sera of elderly individuals. There was a significant correlation with the level of IL-15, another cytokine implicated in the loss of CD28 expression in CD8 ϩ T cells and an inducer of preferential proliferation and functional capabilities of CD4 ϩ CD28 null T cells (20,37).…”
Section: Cd28mentioning
confidence: 90%
“…Recent updates showed that IL-15 preferentially supports proliferation of CD28 null CD4 + T cells over the CD28 + CD4 + T cells. IL-15 not only supports proliferation, but enhances the cytotoxic activity in a shortterm manner by increased IFN-g, granzyme B and perforin production [89]. Other studies supported the differential susceptibility of CD28 null versus CD28 + T cells to other stimuli including cytokines such as IL-12 that may drive Th1 versus Th2 responses.…”
Section: Restoring Immunitymentioning
confidence: 94%
“…CD4 + CD28 − T cells also show no association with antibodies to anti-citrullinated protein, another putative autoantigen in RA, in the serum or synovial fluid (435152). Moreover, accumulating evidence demonstrates that chronic stimulation with proinflammatory cytokines such as TNF-α and IL-15 is responsible for the expansion of CD4 + CD28 − T cells in humans (205354). …”
Section: Clinical Relevance Of Cd4+cd28− T Cellsmentioning
confidence: 99%